DESAIN DAN PENGUJIAN STRUKTUR SATELIT MIKRO LAPAN-TUBSAT - Triharjanto, Robertus Heru (Indonesian Journal of Aerospace, 2006)
The paper discuss about the design and test of the structure of LAPAN-TUBSAT micro-satellite, which is the task done by the writer during his time as the member of LAPAN-TUBSAT integration and test. The discussion includes the design requirment for the structure as mechanical interface and its implementation as well as its design validataion process via test as accordance to the requirement set by the launcher authority.